Bacterial Genetics of Large Mammalian DNA Viruses: Bacterial Artificial Chromosomes as a Prerequisite for Efficiently Studying Viral DNA Replication and Functions - Wussow, Felix; Spieckermann, Tanja; Brunnemann, Anne; Hüske, Linda; Toptan, Tuna; Fickenscher, Helmut (IntechOpen, 2011)
None